The Transition In The Foreign Policy Of India And Its Choices In The Russia-Ukraine War - Rooha Javed , Aisha Javed (Migration Letters, 2024)
The power transition in the world from unipolar to multipolar in the 21st Century has produced multiple reasons for India to develop its foreign policy. India’s Cold War non-alignment foreign policy gave it many opportunities, which it achieved. Within the South Asia region, India is the sole country actively managing and pursuing diplomatic relations with all relevant parties. Consequently, other nations across the globe are closely observing India’s involvement in exerting influence and control over the ongoing Russia-Ukraine war. The expansion of its foreign policy and economy in the present-day geopolitical landscape, notably under the leadership of Prime Mini[1]ster Narendra Mod, has yielded substantial advancements. The Ukraine War has left India’s foreign policy choices in the crosshairs of many opponents and allies. Despite the conflict, India is equipped with the policy of promoting diplomacy while it is maintaining to achieve its national interests at the maximum. This research analyses the depth of India’s changing foreign policy admirations under the umbrella of Neo-Realism by visualising the state’s national interests.